Current Trends in Service Quality: A Transportation Sector Review - Kennedy, Jeffrey (Journal of Applied Business and Economics, 2017)
Studies have emphasized the influence a service employee has on customer perceptions of service quality. Results indicate that employees’ positive and negative behaviors are highly correlated to customer overall satisfaction (Kattara, Weheba, & El-said, 2008). Moreover, research indicates that many service firms fail in delivering service quality to their customers; their frontline employees deliver inferior value to the end user, and this attitude and interaction performed during the service encounter influences customer perceptions of the service delivered. Although many studies have examined general quality management practices, industry-specific studies on quality management practices and factors that influence their success in the shipping industry are rather few (Cheng & Choy, 2007). This review hopes to add to the body of knowledge by positing that truck drivers acting as frontline service employees, play a fundamental role in a company’s assessment of service quality as these drivers deliver cargo to the end user.